ANIMAL PREDATORS AS A CHARACTERISING ELEMENT IN SHORT FOLKLORE FORMS - Babič, Saša (Proverbium - Yearbook, 2024)
Language reflects how we perceive our surroundings. Not only does it enable us to describe them but we also use linguistic expressions to express our ideas metaphorically. In view of this, language stores our observations and stereotypes and carries them as a culture that humans continually create and think about (Pitkin 1972; Bartminski 2005; Tolstaya 2015) in different linguistic forms that are passed down from one generation to the next. Using an ethnolinguistic approach and the help of semiotics, we can take a closer look at the deeper structures and meanings of short folklore forms and, moreover, social stereotypes. This article focuses on wild animals in proverbs, riddles and swear words, and their role in characterisation in short folklore forms.